2w + 3 = 9 <em>subtract 3 from both sides</em>
2w = 6 <em>divide both sides by 2</em>
<h3>w = 3</h3>
X=2 Y=-1 plug them into the equation
-3(2)^2 + 2(-1)^2 + 5(2)(-1) -2(-1) + 5(2)^2 -3(-1)^2
36+4-10+2+100+9
40-10+2+100+9
30+2+100+9
132+9
141
Answer:
x = 1
Step-by-step explanation:
8x + 4 = 12
8x = 8
x = 1
Answer: x = 1/16
Step-by-step explanation:
Since the inverse of a Logarithm is an exponential function, we know that the final solution has to involve an exponential function somewhere in it.
1. log B(2) {x} = -4 || given
2. x = 2 ^ -4 || Logarithm rule that allows you to move the base of the logarithm to the base of the exponent on the other side. For example, if you had log B(5) {x} = 3, the base of 5 would move over to the other side and it would be raised to 3; x = 5^3.
3. x = (1) / (2^4) || Simplify. Use the negative exponent rule. This rule always leaves a numerator of 1, and a denominator of your exponent. In this case, it will be 2 ^ -4, so you will do 2^4 which is 16 and you will put that over 1. Resulting in your final answer of x = 1/16
Answer:
332°
Step-by-step explanation:
Given is an isosceles triangle,
Measures of base angles of an isosceles triangle are equal.
Therefore,
Measure of central angle
= 180° - ( 76° + 76°)
= 180° - 152°
= 28°
Measure of shaded angle
= 360° - 28°
= 332°